Comment on "Simple fluorescence-based detection of Cr(iii) and Cr(vi) using unmodified gold nanoparticles" by M. Elavarasi, S. A. Alex, N. Chandrasekaran and A. Mukherjee, Anal. Methods, 2014, 6, 9554. Issue 14 (21st July 2015) - Hormozi-Nezhad, M. Reza; Mohammadi, J.; Bigdeli, A.
<x xml:space="preserve">Abstract</x> This Comment is an attempt to clarify the difference between Rayleigh scattering peaks and fluorescence peaks in gold nanoparticles.